Risk Perception and Knowledge, Attitudes, and Practices Against COVID-19 in a Hypertensive Population From a Semi-Urban City of Ecuador - Aumala, Teresa; Cardenas, Maria; Vergara, Daniel; Vasconez, Monserrate; Palacios, Ivan; Terán, Enrique (Frontiers in Public Health, 2021)
Background: In an elderly population with hypertension, Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is associated with a higher incidence of mortality and a protracted course of clinical symptoms. Objective: To assess the perceived risk of infection and complications due to COVID-19 in people with hypertension living in a semi-urban city of Ecuador. Methods: A cross-sectional telephone survey of adult outpatients with a previous diagnosis of hypertension in the semi-urban community of Conocoto in Quito, Ecuador was conducted from August to December 2020. Results: A total of 260 adult outpatients, aged 34–97 years, completed telephone surveys. Of this total, 71.5% (n=186) of respondents were female and 28.5% (n=74) were male. Overall, 18.1% believe their risk of infection is “very high,” 55.4% believe it is “high,” 21.5% believe it is “low” and 5% believe it is “very low.” The perceived risk of complications if infected by COVID-19 revealed 21.9% believe their risk is “very high,” 65.0% believe their risk is “high,” 10.4% believe their risk is “low” and 2.7% believe their risk is “very low.” Conclusions: Patients with hypertension are aware of the risks posed by COVID-19 infection and its impact on their health. However, the health system must educate the population on healthy practices and behaviors to avoid COVID-19 infection until the majority of Ecuador’s population can be vaccinated.